Targeted Educational Interventions Increase Human Papillomavirus Vaccine Acceptability and Knowledge [7OP]. (May 2018) - Cory, Lori; Bogner, Hillary; Burger, Robert; Chu, Christina; Ko, Emily
Abstract : INTRODUCTION: We sought to determine if targeted educational interventions can increase human papillomavirus (HPV) vaccine acceptability and knowledge among young women. METHODS: A randomized controlled trial of 256 women aged 12 to 26 at a single institution was completed. Women were randomized to one of three study arms: control (n=85), educational handout (n=84) or educational video (n=87). All subjects completed a survey collecting data on demographics, HPV vaccine preferences and HPV vaccine knowledge following completion of their randomization assignment. Student t test and chi-square tests were applied. RESULTS: Baseline age, race, socioeconomic status and gynecologic history were similar between arms. Post intervention, those who watched the video had higher acceptability for vaccination (51.7%) than the handout (33.3%) or control arms (28.2%) ( P <.01). Those in the video arm also had higher mean HPV vaccine knowledge scores than those in the handout and control arms, respectively, post-intervention (5.7 vs 5.0 vs 2.8, P <.01). Vaccine acceptors were more likely to try to obtain all vaccinations (91.5% vs 75.3%, P <.01) and to recommend HPV vaccination to acquaintances (92.8% vs 43.3%, P <.01) than decliners. Both the video and handout arms reported that the interventions helped them learn (97.7% vs 93.1%, P =.15), but the video arm was more likely to be helpful for deciding about vaccination (86.4% vs 70.5%, P <.01). CONCLUSION: Targeted educational interventions increase HPV vaccine acceptability and knowledge among young women. Future studies may determine if these interventions also increase rates of vaccine uptake and series completion.